PENGARUH BIMBINGAN KELOMPOK DENGAN TEKNIK THINK PAIR SHARE TERHADAP PROKRASTINASI AKADEMIK SISWA DI SMP NEGERI 15 SEMARANG - Farida Zakiyatus Syarifah; Siti Fitriana; Rohastono Ajie (CV. Denasya Smart Publisher, 2024)
This research was motivated by problems related to student academic procrastination at SMP Negeri 15 Semarang. It is said that someone who engages in procrastination is a behavior that is inefficient in using time. The aim of this research is to find out whether there is an influence of the Think Pair Share technical group's guidance services on students' academic procrastination. This type of research is quantitative research with a quasi experimental design. The sample used was 32 students selected randomly using Cluster Random Sampling. The results, through the t test or t-test with the help of SPSS 22, based on the results of the hypothesis test calculations, obtained a significance result (2-tailed) of 0.000 < 0.05. So there is a significant difference between the pretest and posttest. This shows that there is a significant influence on the treatment given in the experimental class. In other words, Ho is rejected and Ha is accepted. On the basis of these calculations, the alternative hypothesis (Ha) reads